EFFECT OF FOCUS STRATEGY ON THE PERFORMANCE OF GUINNESS NIGERIA PLC, ABUJA (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2024)
This study investigates the impact of focus strategies on the performance of Guinness Nigeria Plc, Abuja, with the main goal of evaluating how market and product-focused strategies affect performance. Utilizing a descriptive research design, the study had a population of 260 employees from Guinness Nigeria Plc, Abuja. A stratified random sampling method was employed to select a sample of 188 respondents was determined using the Taro Yamane statistical technique, and data were collected using a well-structured questionnaire. The gathered data were analyzed through regression analysis using SPSS version 27.0 to test the hypotheses. The analysis revealed that market-focused strategies significantly influence the performance of Guinness Nigeria Plc. The study concludes that the implementation of a combination of these focus strategies positively impacts performance. Based on the findings, it is recommended that Guinness Nigeria Plc should continue to develop and implement market-focused strategies. By maintaining a clear strategic direction, the company can further boost employee motivation and overall performance, thereby ensuring sustained productivity and a competitive edge in the market